Impact of arc quenching parameters on surface hardness and microstructure of S45C steel with concave surfaces - Van-Thuc Nguyen; Dang Thu Thi Phan; Huynh Do Song Toan; Tran Thai Son; Pham Son Minh; Nguyen Ho (PLoS ONE, 2025)
This study investigates the effects of arc length, current intensity, travel speed, gas flow rate, and pulse time on surface hardness to better understand the arc quenching of S45C steel with a curved shape. With the standard examination method, increasing the current intensity, Travel speed, and arc length causes the surface hardness to decrease. The surface hardness varies depending on the gas flow rate and pulse time. The Travel speed factor appears to have the greatest effect, followed by the gas flow rate and current intensity. Pulse time and arc length are ranked fourth and fifth, respectively, indicating a smaller impact on surface hardness. The microhardness diagram is divided into four stages: improving, rapid dropping, moderate dropping, and stable. The greatest hardness was 576 HV, with a case depth of 1200 μm. The structure of the arc-hardened sample is composed of hardening zones, HAZ, and base metal. The base metal is composed of ferrite and pearlite, which are the original microstructures of medium-carbon steel. The HAZ is made up of two phases: a brown bainite phase and a brighter ferrite phase. Ferrite, bainite, martensite, and residual austenite phases make up the hardening with a high hardness value area. These phases’ diversity results from their rapid heating and cooling rates as well as the significant variations in cooling rates among depths. The findings of the study on the optimum values of factors such as current intensity at 150 A, Travel speed at 150 mm/min, arc length at 2.5 mm, pulse time at 0.6 s, or gas flow at 10.5 l/min can help engineers to have a closer look at the parameters of this arc tempering technology affecting the surface hardness and their applications. Moreover, the hardness measurement value according to the Taguchi method investigation also shows that the highest value of surface hardness achieved is 42.6 HRC compared to 18 HRC of unhardened surface hardness. In addition, the findings on microstructure also help the applicator to better understand and evaluate the quality of this electric arc method for quenching the surface of S45C steel, thereby making it more useful in the industry.